TANFIDZ THORIQOH AL-TALAQY MA’A FADHIILAH AL-SYAIKH AL-USTADZ AL-DUKTUR MUHAMMAD HASAN USMAN LITARQIYAH NAJAH AL-THULLAB LIGHAIRI NATHIQIINA BIHA FII TA’LIMI AL-LUGHAH AL-‘ARABIYAH FI AL-AZHAR AL-SYARIF: تنفيذ طريقة التلقي مع فضيلة الشيخ الأستاذ الدكتور محمد حسن عثمان لترقية نجاح الطلاب لغير الناطقين بها في تعلم اللغة العربية في الأزهر الشريف - Almannah Wassalwa; Syivaul Hikmatul Hijjiah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
It has become a popular learning method among the students of Al-Azhar University, Cairo, Egypt that this kind of face-to-face study involved the competent teacher. It becomes one of student's choices in order to explore their knowledge so it can increase their opportunity to get the success in their study. This research used the descriptive qualitative analysis with data collection techniques: interview, observation, and documentation. Based on the research results and data analysis that is used by the researcher in the Madyafah Qazaz, Ghamaliah, Egypt, it can be concluded that: 1) The implementation of talaqqi method as a face-to-face learning. In its application, it is began with the book's reading, material extending, concluding, and ended with questions and answers session, 2) The advantages of talaqqi are: improving the student's listening and reading skill well, increasing the student's vocabularies and statements, the learning is simple and easy to understand, improving the student's emphatic, can feel the struggle of ulama, expanding the social network, and getting the knowledge certificate. The disadvantages are: the hot weather that causes students unfocussed, inadequate space, the difficulty faced by female students in giving questions because of their position, the early time, and the teacher was not required to make all of the students understand his learning.